Transparent junctionless electric-double-layer transistors gated by a reinforced chitosan-based biopolymer electrolyte - Jiang, Jie (2013)
Transparent junctionless organic-inorganic hybrid electric-double-layer thin-film transistors are demonstrated using a reinforced solution-processed chitosan-based biopolymer electrolyte as a dielectric layer. The specific feature of such device is that the channel and source/drain electrodes are realized using a thin indium tin oxide (ITO) film without any source/drain junction. A SiO2 film (~5 nm)/chitosan organic-inorganic hybrid bilayer dielectric is found to be an efficient way to improve the stability and performance of the devices. Our results indicate that the transistor gated by organic-inorganic hybrid bilayer dielectric with a thin ITO channel (~10 nm) exhibited a better performance with a lower subthreshold swing (84 mV/dec), a larger ON/OFF ratio (5.5×107), and a smaller bias-stressing threshold voltage shift (ΔVth=0.13 V) . A physical model based on energy diagram with 1-D Poisson equation is proposed to interpret the operating mechanism. These results clearly show that the proposed architecture can provide a new opportunity for the next-generation low-voltage low-cost device design.